Ten unpublished Dante files by Edoardo Sanguineti: First Reconnaissance in the Heirs of the Wunderkammer Fund (Prassi Ecdotiche della Modernità Letteraria, 2021)
In the early months of 2021 Inter-University Study Center Edoardo Sanguineti got new archival resources from Edoardo Sanguineti’s studio, then collected in the Eredi Sanguineti fund. In the collection of papers, ten typescript tiles stand out, similar to those intended for UTET dictionaries, but probably meant for other destination: indeed, in the ten unpublished tiles the author focused on Dante’s verses honored in Franco Sacchetti’s and Girolamo Savonarola’s works.
Keywords: Edoardo Sanguineti; Dante Alighieri; lexicography; Divina Commedia; Franco Sacchetti; Girolamo Savonarola